(untitled) (Praxis Educativa, 2018)
This text tries to reflect on the very potentiality of education thinking in what refers to there signification of schemes from the reading of “A Manifesto for education”. This manifesto can be understood as an adolescent ideality, which not only begins, but also always sends in disappointment –in this evil of ideality. The ideality pursued by every manifesto can lead to immobility and disappointment, without even trying to break down structuring schemes. The article that is presented will try to approach this question from our own thoughts about the critique of ideality and there flections that the manifesto in question invites us to make. In some way it gives us the possibility to think and think educationally. But what does that mean, exactly? To reach the meaning of thinking about education, we need to consider what is implicit in holding “what is” and “what is not” in tension. This will focus on the last section of the work.